Impact of internet plus health education on urinary stoma caregivers in coping with care burden and stress in the era of COVID-19 - Fan, XuFei; Li, HaiYan; Lai, LiYa; Zhou, XiaoFeng; Ye, XiangXiang; Xiao, HaiNiao (Frontiers in Psychology, 2022)
Objective To explore the impact of “Internet Plus Health Education” on coping with care burden and pressure in urinary stoma caregivers in the era of COVID-19. Materials and methods Eighty caregivers of patients with urinary ostomy were equally randomized to experimental and control groups. Caregivers in the experimental group received digital nursing education intervention, which involved nursing intervention of Internet Plus Health Education (IPHE), and those in the control group received conventional care instructions. Six months later, care burden and emotional pressure were assessed in all caregivers using the Zarit Caregiver Burden Interview (ZBI) and the Simplified Coping Style Questionnaire (SCSQ). Results Before the intervention, the ZBI and SCSQ scores were comparable between both groups (p > 0.05). After the intervention, the ZBI scores in the experimental group were significantly higher than in the control group and vice versa for SCSQ scores (p < 0.01). Furthermore, after the intervention, the family care satisfaction scale (FCSS) of the experimental group was significantly higher than the control group. Conclusion Providing “Internet Plus Health Education” to urinary stoma caregivers can reduce their care burden and enhance their pressure-coping ability in the COVID-19 era.